12)
2x^2 - 20x + 89 = - 87
2x^2 - 20x = - 87 - 89
2x^2 - 20x = - 176
Dividing both sides of the equation by 2, we have
x^2 - 10x = - 88
We would add the square root of half the coefficient of x to both sides. We would add (- 5)^2 to both sides. We have
x^2 - 10x + (- 5)^2 = - 88 + (- 5)^2
(x - 5)^2 = - 88 + 25 = - 63
Taking square root of both sides, we have
![\begin{gathered} x\text{ - 5 = }\pm\sqrt[]{-\text{ 63}} \\ x\text{ = 5 }\pm\sqrt[]{-\text{ 63}} \\ x\text{ = 5 + 63i or x = 5 - 63i} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/35aalf4kr4bdmmc6fv6ztxso7m7goxm5ml.png)